1994
DOI: 10.1128/jb.176.17.5320-5329.1994
|View full text |Cite
|
Sign up to set email alerts
|

spo0J is required for normal chromosome segregation as well as the initiation of sporulation in Bacillus subtilis

Abstract: The spoOJ gene of BaciUlus subtilis is required for the initiation of sporulation. We show that the sporulation defect caused by null mutations in spoOJ is suppressed by a null mutation in the gene located directly upstream from spoOJ, soj (suppressor of spoOJ). These results indicate that Soj inhibits the initiation of sporulation and that SpoOJ antagonizes that inhibition. Further genetic experiments indicated that Soj ultimately affects sporulation by inhibiting the activation (phosphorylation) of the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
466
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 349 publications
(495 citation statements)
references
References 54 publications
19
466
1
Order By: Relevance
“…Recently, important progress has been made in the understanding of the active chromosomal segregation process in vegetative and sporulating B. subtilis cells (Ireton et al, 1994;Sharpe and Errington, 1996;Glaser et al, 1997;Lin et al, 1997;Webb et al, 1997). It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, important progress has been made in the understanding of the active chromosomal segregation process in vegetative and sporulating B. subtilis cells (Ireton et al, 1994;Sharpe and Errington, 1996;Glaser et al, 1997;Lin et al, 1997;Webb et al, 1997). It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997). Because accurate segregation is affected in spoOJ mutant strains (Ireton et al, 1994;Sharpe and Errington, 1996), the SpoOJ protein was a prime candidate for being involved in the chromosomal segregation process. Using in vivo cross-linking techniques, the SpoOJ protein was recently shown to be associated with short DNA sequences containing the same DSE (Lin and Grossman, 1998) that is repeatedly present in the 29 genome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations